Opphavet til kvinnenamnet "Rise" i Sunnfjord - Kinn, Torodd (NAMN OG NEMNE, 2023)
The female name Rise (or Risse) was given to girls in the Sunnfjord area during the greater part of the 19th century. Other areas where Rise was used are very limited, mostly Vestfold and Buskerud. Norsk personnamnleksikon (NPL; Kruken & Stemshaug 2013) states that this name stems from Regi(t)se. This article shows that Rise in Sunnfjord is a short form of Iverisse (or Iverise), a name that was used in the same Sunnfjord area as Rise from the middle of the 18th century. The first girls called Iverisse were the children of farmers, but they were clearly named for a recently deceased priest, Iver Myhlenphort. The name had been used in his family earlier. His maternal aunt was the first known bearer of the name Iverise mentioned in NPL. NPL states that Iverise is derived from the male name Iver, which is most probably correct. Thus, Rise in Sunnfjord is a short form of Iverise, derived from Iver.